Landscape is Now (Again): Cosmoramic Views from the Arctic Anthropocene - Cheetham, Mark (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2025)
Landscape continues to be both practiced and critiqued, a form and concept that remains simultaneously compelling and uncertain. Can we reinvent landscape as a category in visual studies even as we acknowledge its colonizing manifestations in Europe and the Americas and current concerns about a changing climate through the lens of the Anthropocene? I metaphorically extend the magnified landscapes of the Cosmorama, an eclipsed 19th-century visual entertainment, to focus an examination of Arctic landscapes from the 18th century to the present. I claim that every cosmoramic landscape in my sequence implies a view to the planet as a whole and that landscape is more relevant now than ever because of attempts to define and comprehend planetary climate emergency created and revealed in the Anthropocene.